Human trafficking for criminal exploitation: Effects suffered by victims in their passage through the criminal justice system. Issue 1 (January 2019) - Villacampa, Carolina; Torres, Núria
The victim-centred approach to human trafficking emphasises the protection of victims and respect for their rights. For this protection to be effective, victims must be treated as such in their passage through the criminal justice system, which can be complex with forms of trafficking that are still relatively unknown, such as trafficking for criminal exploitation. Based on 37 in-depth interviews with Spanish practising criminal justice and victim assistance services professionals, this paper analyses the effects that the failure to identify these types of victims has on them as they make their way through the criminal justice system, paying particular attention to the degree to which the aforementioned professionals recognise the principle of non-punishment.